Da (des)responsabilidade docente pelo mundo ao Amor Mundi em Hannah Arendt - Morello, Eduardo (2014)
This dissertation thematizes the relationship between teaching and world in Hannah Arendt. The starting point of the investigation is Arendt's observation that this relation is disrupted with the advent of social sphere in modernity, so that the only "common" concern to the individuals happens to be the life, the survival and the well-being, occurring, thus, the inversion of world and life. Based on this problematic, the central question is how to educate the newcomers in a world where the only concern that is needed is with life, with survival and with well-being. Although Arendt does not provide answers, she is implacable in asserting that in education teachers should take a dual responsibility, namely, with the world and newcomers. Based on this position of the author, it is formulated the hypothesis that a possible reconciliation among teaching and world can be sought in the notion of responsibility for the world understood as a condition of possibility for teaching authority, as well as manifestation of amor mundi in education. In order to develop it, is carried out research of bibliographical nature, guided by an analytical-reconstructive procedure of delimited arendtians texts and secondary literature related to the research problematic. The work is structured in three chapters: in the first one, we discuss some senses of Arendt's concept of world in the book The human condition and in the essay "The crisis in education"; on the second, we analyze the field of social sphere on the pre-political sphere of education as one of the main conditions that led teachers to refuse themselves to take responsibility for the world front of newcomers; at last, on the third one, it is formulated a possibility of reconciliation between teaching and world as from the notion of responsibility for the world understood in a double aspect: as a condition of possibility for the teaching authority and as a manifestation of amor mundi in education